A Systematic Workflow for Compliance Testing of Emerging International Classwide Restrictions on PFAS - Vestergren, Robin; Appelblom, Anders; Bălan, Simona A.; Brandsma, Sicco H.; Bruton, Thomas A.; Cousins, Ian T.; Gauthier, Jeremy R.; Heggelund, Audun; Ivarsson, Jenny; Kärrman, Anna; Melymuk, Lisa; Olisah, Chijioke; et al. (Environmental science & technology, 2024)
The poorly reversible risks to human health and ecosystems from contamination with per- and polyfluoroalkyl substances (PFAS) have led many researchers and regulators worldwide to call for a classwide ban of these so-called forever chemicals. As part of the EU Chemicals Strategy for Sustainability, the national authorities of five European countries submitted a broad restriction proposal on PFAS under REACH in January 2023. This restriction proposal is unique in its scope by including the vast majority of uses for >10 000 substances that meet the OECD definition of PFAS. (1) In parallel, several countries and multiple states in the United States have proposed or enacted broad PFAS restrictions for all non-essential uses or for specific uses and reporting requirements for a range of consumer products. Although the regulatory frameworks underpinning these restrictions contain many differences, the proposed restrictions have the common objective to ban the intentional use of all PFAS and thus avoid regrettable substitution with other PFAS. Given that the proposed restrictions apply to chemical products and articles (both hereafter termed simply “products”) that are imported from other states, countries, or regions, they may also trigger substitution and an increased demand for supply chain information on a global level. Direct communication with manufacturers and distributors is typically the primary approach for companies to ensure compliance with chemical regulations. Nevertheless, companies and authorities require reliable analytical methods to independently verify supply chain information and capture products that are noncompliant with PFAS restrictions.